Value added productivity performance of the peninsular Malaysian wood sawmilling industry - Pang, Suet Kum; H'ng, Paik San; Chai, Lai Yee; Lee, Seng Hua; Md. Tahir, Paridah (North Carolina State University, 2015)
Value added manufacturing activity in the wood sawmilling industry of Peninsular Malaysia is important for employment opportunities, particularly for low income citizens living in this rural area, to provide returns to the local economy while being environmentally sustainable. This paper is a review on the value added wood sawmill industry in Peninsular Malaysia, using the value of major import and exports of major timbers products and forested area in Peninsular Malaysia over the period 2003 to 2012. The productivity performance measures that are based on the concept of value added are emphasized in this paper. The value added in wood sawmill industry was found to increase from year 2003 to 2012. Consequently, Malaysia is moving on the right path to achieve the goal of National Timber Policy 2020, transforming the timber industry into high value addition industry. However, further analysis using the value added productivity measure found that the value addition rely on international timber price rather than skilled workers.